Um modelo para determinação de irrigação suplementar - Bernardo , Salassier; Hill, Robert W (Revista Ceres, 2025)
Data from 12 stations in the São Francisco basin were used in the model for 12 soil moisture storage capacities. From the model output, curves of irrigation period, number of irrigations, and annual supplemental irrigation and effective rainfall versus net depletion were produced for each region. The usefulness of these curves for designing supplemental irrigation systems was demonstrated.